Studies on the workability of cement-lime-sand mortars - Kant Singh V.; Kumar Khare V. (My University, 2025)
Workability of cement, lime and sand mortars was studied by the measurement of flow on a flow table. Effects of cement and sand proportions were investigated by taking various mixes from 1:1.0 to 1:5.0 cement:sand mortars. 1:2.5, 1:3.0 and 1:3.5 cement: Sand mixes were further studied by the use of lime as workability aid. It was found that mixes of cement and sand from 1:1.0 to 1:4.0 ratio behave like plastic masses and workability increases by increase in water content without any yield point. 1:4.5 and 1:5.0 cement: sand mixes gave certain yield values. Overall workability of various mixes with different water content has shown that workability increases from 1:1.0 to 1:2.0 and thereafter it decreases from 1:2.5 to 1:5.0 cement: sand mixes. The effect of lime was that it increases the workability in each case and the effect is more marked at higher lime contents in the mixes. © 1978, Taylor & Francis Group, LLC.